2023
DOI: 10.1038/s43247-023-00918-y
|View full text |Cite
|
Sign up to set email alerts
|

Mantle-to-crust metal transfer by nanomelts

Abstract: The transfer of chalcophile metals across the continental lithosphere has been traditionally modeled based on their chemical equilibrium partitioning in sulfide liquids and silicate magmas. Here, we report a suite of Ni-Fe-Cu sulfide droplets across a trans-lithospheric magmatic network linking the subcontinental lithospheric mantle to the overlying continental crust. Petrographic characteristics and numerical calculations both support that the sulfide droplets were mechanically scavenged from the mantle sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…Намечающееся в последнее время интенсивное развитие «микрометаллогенического» подхода к изучению петрологии и металлогенического потенциала горных пород требует разработки надежных методов определения химического состава и фазовой принадлежности обнаруживаемых в этих породах микровключений. Эти методы направлены как на прецизионное определение химического состава микровключений [например, 35,54], так и на экспрессную полуколичественную оценку состава с целью их минералогической идентификации, продемонстрированную, в частности, в настоящей статье. Ее использование при изучении анкарамитов и содержащихся в них перидотитовых ксенолитов из Авачинского вулкана на Камчатке, а также пород основного-ультраосновного массива Ильдеус в Становой складчатой области позволило получить новые данные о петрологических процессах в мантийно-коровом субстрате под активной вулканической дугой и об особенностях эволюции рудно-магматической системы под древней активной континентальной окраиной.…”
Section: заключениеunclassified
“…Намечающееся в последнее время интенсивное развитие «микрометаллогенического» подхода к изучению петрологии и металлогенического потенциала горных пород требует разработки надежных методов определения химического состава и фазовой принадлежности обнаруживаемых в этих породах микровключений. Эти методы направлены как на прецизионное определение химического состава микровключений [например, 35,54], так и на экспрессную полуколичественную оценку состава с целью их минералогической идентификации, продемонстрированную, в частности, в настоящей статье. Ее использование при изучении анкарамитов и содержащихся в них перидотитовых ксенолитов из Авачинского вулкана на Камчатке, а также пород основного-ультраосновного массива Ильдеус в Становой складчатой области позволило получить новые данные о петрологических процессах в мантийно-коровом субстрате под активной вулканической дугой и об особенностях эволюции рудно-магматической системы под древней активной континентальной окраиной.…”
Section: заключениеunclassified
“…This concept triggered a cascade of subsequent studies and gained increasing popularity ( 26 28 ), supporting previous studies on the potential role of volatiles in metal transport ( 29 33 ). The adherence of sulfide globules to gas bubbles may enhance their transport, especially in shallow magmatic-hydrothermal systems ( 34 ); however, the extension of this “bubble” model of sulfide mobilization to deep systems ( 10 , 11 ), where gas bubbles are unlikely to exist due to their high solubilities at high pressures, might not be suitable.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was initially put forward based on experimental studies that demonstrated the strong affinity of vapor bubbles for sulfide globules ( 21 ). Originally confined to experimental studies and numerical modeling, only a few years later this compound droplet model was gradually applied to natural systems ( 10 , 11 , 24 , 25 ). According to this hypothesis, as magma ascends, the adherence of vapor bubbles to the surfaces of sulfide globules results in the formation of relatively buoyant compound droplets that resemble hot-air balloons transporting metal-rich sulfide cargos ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of economic geology, nanomaterials may include atomic clusters, mineral nanoparticles (1–100 nm; NPs hereafter), nanominerals, nanofluids, and nanomelts, usually constituted by a wide suite of metals 1 3 . In the last decade, an ever-increasing amount of evidence has documented nanomaterials in hydrothermal solutions 4 , thus questioning the traditional paradigm that ligands (e.g., chloride- and bisulfide-bearing) are the sole efficient metal carriers in ore-forming fluids 5 .…”
Section: Introductionmentioning
confidence: 99%